Associated factors for discontinuation of statin use one year after discharge in patients with acute coronary syndrome in China. Issue 9 (14th September 2022) - Xie, Gaoqiang; Myint, Phyo Kyaw; Sun, Yihong; Li, Xian; Wu, Tao; Gao, Run-lin; Wu, Yangfeng
Abstract : Objectives: To determine the associated factors for discontinuation of statin use 1 year after discharge in patients who survived from acute coronary syndrome (ACS) in China. Settings: 75 hospitals across China. Design: A cohort follow-up study. Participants: The study included 10 337 patients with ACS hospitalised in 2007–2010 and discharged with statins from 75 hospitals in China in the Clinical Pathways for Acute Coronary Syndromes in China Study-Phase 2 (CPACS-2), who were followed-up at 6 and 12 months postdischarge. Primary outcome measures: The primary outcome was the discontinuation of statin use defined as not in current use of statin at either 6-month or 12-month follow-up. Results: Multivariable logistic regression model showed that patients who did not have cholesterol measurement (adjusted OR=1.29; 95% CI: 1.10 to 1.50) and patients with either higher (1.27; 1.13 to 1.43) or lower dose of statin (1.22; 1.07 to 1.40), compared with those with standard dose, were more likely to discontinue the use of statin. In addition, patients on the CPACS-2 intervention pathway (adjusted OR=0.83; 95% CI: 0.74 to 0.94), patients with medical insurance (0.75; 0.67 to 0.85), history of hypertension (0.83; 0.75 to 0.92), high low-density lipoprotein cholesterol (0.70; 0.57 to 0.87) at the baseline, prior statin use (0.73; 0.63 to 0.84), use of atorvastatin (0.78; 0.70 to 0.88) and those who underwent percutaneous coronary intervention or coronary artery bypass grafting during hospitalisation (0.47; 0.43 to 0.53) were less likely to discontinue statin use. The 1-year statin discontinuation rate decreased from 29.5% in 2007–2008 to 17.8% in 2010 (adjusted OR=0.60; 95% CI: 0.51 to 0.70). Conclusion: Implementing clinical pathway, enhancing medical insurance coverage, strengthening health education in both physicians and patients, using statin at standard dosage may help improve the adherence to statin use after discharge in Chinese patients with ACS. Trial registration number: Australian New Zealand Clinical Trials Registry (ACTRN12609000491268).